Marketing Control by the Method of Balanced Scorecard - Krikščiūnienė, Dalia (Ekonomika, 2000)
The common approach to solving marketing management problems is improvement of the planning process. Yet this is not confirmed by results of recent research, made at Fortune 500 companies, which has shown that 9 enterprises of to fail to achieve strategic goals, stated in their marketing plans. The possible solution is wider introduction of marketing information systems for evaluation and control processes of the marketing management activities.The objective of the article is to discuss the methods of marketing control function, their implementation with the help of marketing information system. The possibility to apply the balanced scorecard for marketing control is overviewed from the perspective of eliminating the drawbacks of traditional methods of control. The balanced scorecard offers a fourperspective organizational alignment, which allows to effectively integrate marketing indicators for control process.The balanced scorecard is suggested to be integrated into MIS for the computerized marketing control, with the use of modem information technologies (IT). The contemporary IT (data warehousing, OLAP) extend information analysis and decision-support possibilities for implementing control function in MIS.